2019
DOI: 10.1172/jci128527
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation within TERT promoter upregulates TERT expression in cancer

Abstract: Of the 1352 samples in the cohort, which were provided by multiple collaborators, four samples of breast tissue for which DNA was analyzed were a part of another study. Since these samples did not go through the same rigorous screening process, including pathology review and extraction of DNA from paraffin tissues, that was applied to all other samples, the authors are less confident in their exact identity and have decided to retract them from the study. This does not change the message of the paper, but resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 0 publications
4
120
0
Order By: Relevance
“…Our previous study performed on APL cell lines identified two distinct functional domains in hTERT promoter, one distal and one proximal, differentially methylated (Azouz et al , 2010). These results are in agreement with the recent identification of the TERT hypermethylation oncologic region, a 433‐bp genomic region located −159 to −591 bp upstream the TSS (Castelo‐Branco et al , 2016; Leao et al , 2019; Lee et al , 2019), as a potential biomarker in several cancers. This region is of major importance, because its methylation status correlates with hTERT expression.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study performed on APL cell lines identified two distinct functional domains in hTERT promoter, one distal and one proximal, differentially methylated (Azouz et al , 2010). These results are in agreement with the recent identification of the TERT hypermethylation oncologic region, a 433‐bp genomic region located −159 to −591 bp upstream the TSS (Castelo‐Branco et al , 2016; Leao et al , 2019; Lee et al , 2019), as a potential biomarker in several cancers. This region is of major importance, because its methylation status correlates with hTERT expression.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a close genomic-epigenetic interaction is required for telomerase activation, like TPE-OLD-mediated TERT transcription. Interestingly, TERT promoter methylation is required for cancer cells to activate TERT transcription, while TERT induction in turn promotes the aberrant methylation by upregulating the expression of DNA methyltransferases, which forms a positive feedback loop [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…2) [21,22]. The TERT harbors a single promoter embedded in a CpG island (−1800 to +2300 relative to ATG), while the proximal core promoter is within a 330 bp upstream and 37 bp downstream from ATG (−330 to +37) [23][24][25][26]. Remarkably, the TERT promoter region is rich with biding motifs for multiple transcription factors including the MYC oncogene (E-box) and Sp1 (GC box), but lack TATA and CAAT boxes [21,27].…”
Section: The Tert Gene and Its Promoter And Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations